2019
DOI: 10.1038/s41598-019-54514-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting novel genomic regions linked to genetic disorders using GWAS and chromosome conformation data – a case study of schizophrenia

Abstract: Genome-wide association studies identified numerous loci harbouring single nucleotide polymorphisms (SNPs) associated with various human diseases, although the causal role of many of them remains unknown. In this paper, we postulate that co-location and shared biological function of novel genes with genes known to associate with a specific phenotype make them potential candidates linked to the same phenotype (“guilt-by-proxy”). We propose a novel network-based approach for predicting candidate genes/genomic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…When directly comparing NT5E mRNA expression levels between control and patient populations, this difference was significantly different. There is otherwise limited information describing a role for NT5E in schizophrenia biology but one genome-wide association study identified a single nucleotide polymorphism (rs217331) in the SNAP91 gene that associated with the risk of developing schizophrenia; the promoter region of SNAP91 interacts with the promoter of NT5E at the structural level (28). An adenosine hypothesis for schizophrenia has been described that integrates dysfunction in both dopaminergic and glutamatergic signaling (29).…”
Section: Discussionmentioning
confidence: 99%
“…When directly comparing NT5E mRNA expression levels between control and patient populations, this difference was significantly different. There is otherwise limited information describing a role for NT5E in schizophrenia biology but one genome-wide association study identified a single nucleotide polymorphism (rs217331) in the SNAP91 gene that associated with the risk of developing schizophrenia; the promoter region of SNAP91 interacts with the promoter of NT5E at the structural level (28). An adenosine hypothesis for schizophrenia has been described that integrates dysfunction in both dopaminergic and glutamatergic signaling (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, GWAS variants turn out to be located mainly outside genes, with only a minor fraction impacting nearby genes ( Fadason et al, 2017 ; Mumbach et al, 2017 ; Fu et al, 2018 ). In a 3D space, variants likely affect more genes than projected and new eQTLs can be identified ( Fadason et al, 2018 ; Buxton et al, 2019 ). Integration of 3D genomic perspectives, including LAD information, into GWAS studies may enhance identification of new genes and mechanisms underlying complex diseases, and in designing new treatments.…”
Section: Perspectivesmentioning
confidence: 99%
“…On the basis of linkage disequilibrium and allele frequency, researchers have identi ed regions associated with complex traits, shedding light on various evolutionary patterns in uencing these trait loci 8 . Furthermore, the integration of 3D structure data with GWAS signals has highlighted genes in close proximity to known phenotypic sites, facilitating the identi cation of potentially schizophrenia-associated genomic regions 9 . Additionally, sequences like tandem or proximal repeats, which are intricate regions of eukaryotic genomes but pose challenges for molecular identi cation because of their high similarity, play crucial roles in understanding human diseases, developmental processes, and environmental adaptability 10 .…”
Section: Introductionmentioning
confidence: 99%